Politico-ideological violence in Lebanon: The narrative embeddedness of grievances - Ajil, Ahmed (Frontiers in Human Dynamics, 2022)
This paper presents the findings from doctoral research conducted between 2018 and 2020 on politico-ideological moblisation and violence in relation to causes and conflicts in the Arab World. It focuses on interviews conducted in Lebanon with individuals engaged in violent action or sympathising with violent groups. Ideologically, the sample comprised a variety of orientations, including Christian right-wing, Salafi-jihadist and Shia militantism. The socio-economic, ethno-racial and political grievances expressed by interviewees are analysed in-depth and the importance of collective memories, identities and narratives is elaborated on. It is argued that grievances, in order to be sustained over time and space, need to decomplexify reality by allowing for analysis to escape to the global, the collective and the past. Grievances are narratively embedded in a framework that simplifies reality in order to pinpoint injustices and suggest straightforward actions for remedying them.